Comprehensive modeling study of ozonolysis of oleic acid aerosol based on real‐time, online measurements of aerosol composition. Issue 8 (18th April 2017) - Gallimore, P. J.; Griffiths, P. T.; Pope, F. D.; Reid, J. P.; Kalberer, M.
Abstract: The chemical composition of organic aerosols profoundly influences their atmospheric properties, but a detailed understanding of heterogeneous and in‐particle reactivity is lacking. We present here a combined experimental and modeling study of the ozonolysis of oleic acid particles. An online mass spectrometry (MS) method, Extractive Electrospray Ionization (EESI), is used to follow the composition of the aerosol at a molecular level in real time; relative changes in the concentrations of both reactants and products are determined during aerosol aging. The results show evidence for multiple non‐first‐order reactions involving stabilized Criegee intermediates, including the formation of secondary ozonides and other oligomers. Offline liquid chromatography MS is used to confirm the online MS assignment of the monomeric and dimeric products. We explain the observed EESI‐MS chemical composition changes, and chemical and physical data from previous studies, using a process‐based aerosol chemistry simulation, the Pretty Good Aerosol Model (PG‐AM). In particular, we extend previous studies of reactant loss by demonstrating success in reproducing the time dependence of product formation and the evolving particle size. This advance requires a comprehensive chemical scheme coupled to the partitioning of semivolatile products; relevant reaction and evaporation parameters have been refined using our new measurements in combination with PG‐AM. Key Points: Extractive electrospray ionization mass spectrometry can be used to assess reaction kinetics in oleic acid aerosols The most important sinks for Criegee intermediates formed during oleic acid ozonolysis are isomerization and secondary ozonide formation The Pretty Good Aerosol Model can reproduce measurements of evolving reactant loss, product formation, and particle size change